Transcription and translation contribute to gene locus relocation to the nucleoid periphery in E. coli - Sora Yang (Nature Portfolio, 2019)
Transcription and translation are coupled in bacteria. Here, the authors show that the movement of a gene locus to the nucleoid periphery correlates with transcription, and the effect is potentiated by translation.